(untitled) (Herald of Journalism, 2022)
Facebook and Instagram have become not only platforms for the exchange of information on the Internet, but also platforms for discussion of any events taking place in the world. The purpose of the research is to determine the role of social networks in the formation of pluralism during political events in the country, as well as how powerful a tool they are currently. As a result of the study it was found that the population is still afraid to express their opinions freely. After all, all comments to the post of representatives of the official group are recorded from a fake account. It is also reported that some event occurred there, only in the informational state. And independent authors tend to have a broad discussion and differentiation of what was on their pages. This will contribute to a comprehensive understanding of the circumstances by the population. However, unfortunately, only the position of the author himself is given here. As a result, the population is also limited to receiving information unilaterally. Therefore, representatives of official groups should used the most comprehensive transmission of information. Instagram and Facebook’s role in shaping public opinion and information literacy of citizens in connection with what happened in the country in January of this year will be assessed in the article. Information literacy is not only the free expression of one’s opinion, but also the correct sorting of information perceived from the outside world, critical understanding of the posts of people reading on the social network, competent consumption of information content. In the absence of information literacy, a person cannot form his own opinion and become the leader. This, in turn, will lead to the spread of fake news, conflict within the state and panic. The article presents statistical data. Main methods are comparison, historical comparison. The opinions of foreign experts are also given. The level of information consumption would increase if society could trust only official data and be critical towards any information in social networks. In this context, it is always necessary for the official media to publish information about topics that cause panic first in social networks and comment in a timely manner. Keywords: information literacy, public opinion, fake news, social networks, official media, political conflict.